Cleopatra : a life - Schiff, Stacy (Little, Brown and Co., 2010)
The Pulitzer Prize-winning biographer brings to life the most intriguing woman in the history of the world: Cleopatra, the last queen of Egypt. Though her life spanned fewer than 40 years, it reshaped the contours of the ancient world.